2010
DOI: 10.3109/10253891003713765
|View full text |Cite
|
Sign up to set email alerts
|

Salivary cortisol responses to a psychosocial laboratory stressor and later verbal recall of the stressor: The role of trait and state rumination

Abstract: This study investigated whether trait rumination predicts greater increases in salivary cortisol concentration and delayed recovery in response to a standardized, acute laboratory psychosocial stressor (modified Trier Social Stress Test). It also tested whether trait and state rumination predict reactivation of the cortisol response during later verbal recall of the stressor. Fifty-nine undergraduates (31 females; 28 males) completed the stress protocol and returned 2 weeks later for a surprise interview about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 34 publications
6
73
2
Order By: Relevance
“…In addition, morning cortisol awakening responses were greater for those who reported ruminating the day before, compared to those who did not ruminate [33]. In contrast, of the nine studies that tested associations between trait rumination and cortisol concentrations ( Table 2), only two reported positive associations [28,34]. Of the remaining seven studies, one found a negative association [17], three reported no associations [27,33,35], and three found mixed associations (positive and null [36,37] or negative and null [38,39]) between trait rumination and cortisol outcomes.…”
Section: Associations Between Cortisol and Trait And State Measures Omentioning
confidence: 46%
See 2 more Smart Citations
“…In addition, morning cortisol awakening responses were greater for those who reported ruminating the day before, compared to those who did not ruminate [33]. In contrast, of the nine studies that tested associations between trait rumination and cortisol concentrations ( Table 2), only two reported positive associations [28,34]. Of the remaining seven studies, one found a negative association [17], three reported no associations [27,33,35], and three found mixed associations (positive and null [36,37] or negative and null [38,39]) between trait rumination and cortisol outcomes.…”
Section: Associations Between Cortisol and Trait And State Measures Omentioning
confidence: 46%
“…Specifically, cortisol concentrations were higher for those with greater rumination on stressful laboratory tasks [17,28,30,31] or recent interpersonal transgressions [32]. In addition, morning cortisol awakening responses were greater for those who reported ruminating the day before, compared to those who did not ruminate [33].…”
Section: Associations Between Cortisol and Trait And State Measures Omentioning
confidence: 89%
See 1 more Smart Citation
“…Our findings of significant associations between blunted cortisol reactivity and higher ISBF total scores are in line with previous research. They positively relate to psychological concepts that have been associated with lower cortisol stress reactivity, such as lower levels in psychological stress reactivity (as measured by the Stress-Reactivity Scale, (P. Schulz et al, 2005), higher perceived social support (Seeman and McEwen, 1996;Wirtz et al, 2009), and lower rumination as measured by the Irritation Scale (Zoccola et al, 2010). Also, relaxation techniques such as progressive muscle relaxation have been shown to acutely decrease activity of stress-response systems, thus possibly preparing for either active stress management or regeneration (Cruess et al, 2000;Jones, 2002, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, rumination has been linked with greater cortisol reactivity and delayed recovery in response to social stress and rejection in adults [15,16,17]; and cardiovascular reactivity to interpersonal stress in children [18]. Therefore, depressed adolescents' higher on trait rumination may be more negatively impacted by peer feedback as the tendency to perseverate on past social 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 RUMINATION AND PUPILLARY RESPONSE 5 interactions places them at greater risk for a longer and more severe course of depression.…”
Section: Manuscriptmentioning
confidence: 99%